The effects of alcohol consumption and its associations with disease activity among 979 patients with inflammatory arthritis - Phil Gallagher (RMD Open, 2021)
Objective The role of alcohol in inflammatory disease remains debated. This study explores the relationship between alcohol and disease activity in patients with inflammatory arthritis.Methods Patients attending a rheumatology clinic between 2010 and 2020 were prospectively followed. Information on demographics, alcohol use, smoking habits and disease outcome measures were collected from these patients. Statistical analysis included univariate and multivariate linear and binary logistic regressions, Mann-Whitney U tests and one-way analysis of variance with Tukey’s honest significant difference (HSD) test.Results Of the 979 analysed patients, 62% had rheumatoid arthritis (RA), 26.7% had psoriatic arthritis (PsA) and 11.2% had ankylosing spondylitis. Mean DAS28-CRP (Disease Activity Score 28 - C-reactive protein) in RA and PsA at 1 year was 2.96±1.39, and 64.2% of patients were in remission (DAS28-CRP ≤2.6 or BASDAI (Bath Ankylosing Spondylitis Disease Activity Index) ≤4). Both male gender and risky drinking (>15 units of weekly alcohol) were significantly associated with remission. Compared with women, men had an OR of 1.8 (1.1, 2.5) (p=0.034) for any alcohol consumption and 6.9 (4.7, 9.1) (p=0.001) for drinking at least 15 weekly drinks. When adjusted for gender, there was no association between alcohol and disease activity. Yet, when adjusted for alcohol consumption, gender still significantly influenced disease activity.Conclusion While it may appear that alcohol is linked to remission in inflammatory arthritis, when adjusted for gender, it is not. Men with inflammatory arthritis drink significantly more than women and have less severe disease activity.